2018
DOI: 10.1016/j.biomaterials.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

3D-3-culture: A tool to unveil macrophage plasticity in the tumour microenvironment

Abstract: The tumour microenvironment (TME) shapes disease progression and influences therapeutic response. Most aggressive solid tumours have high levels of myeloid cell infiltration, namely tumour associated macrophages (TAM). Recapitulation of the interaction between the different cellular players of the TME, along with the extracellular matrix (ECM), is critical for understanding the mechanisms underlying disease progression. This particularly holds true for prediction of therapeutic response(s) to standard therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(173 citation statements)
references
References 81 publications
3
169
0
1
Order By: Relevance
“…To unravel the role of monocytes as EPCs in cancer context, we employed a 3D co-culture system [44] of human breast cancer cells (HCC1954) and human monocytes. In co-culture, hvWF positive cells also expressed FN ( Figure 5A), which suggested that monocytes are differentiating into ECs.…”
Section: Monocytes Are Active Stakeholders In Neo-vasculature Networkmentioning
confidence: 99%
“…To unravel the role of monocytes as EPCs in cancer context, we employed a 3D co-culture system [44] of human breast cancer cells (HCC1954) and human monocytes. In co-culture, hvWF positive cells also expressed FN ( Figure 5A), which suggested that monocytes are differentiating into ECs.…”
Section: Monocytes Are Active Stakeholders In Neo-vasculature Networkmentioning
confidence: 99%
“…However, the cell death response was decreased to around 30% in day 10 spheroids. The decrease in ferroptosis could be caused by an increase in complexity of spheroids over time and secretion of extracellular matrix [16]. For day 1 SKOV spheroids, approximately 85% of cell death was observed after stimulation with ML-162.…”
Section: Validation Of 3delta: Quantification Of Ferroptotic Cell Deathmentioning
confidence: 99%
“…Therefore, with regard to the responses to therapy, including to cell death, 3D structures are better test models for drug screening compared to 2D monolayers [13].Spheroids are one of the most widely used 3D models and can be formed by seeding cells in nonadherent plates allowing for self-assembly ( Figure 1A) [7]. In spheroids, the ECM can be produced by cells, which acts as an extra barrier for drugs to cross in order to induce tumour cell death [14][15][16]. Moreover, the compactness and stiffness of spheroids resemble the in vivo hypoxic tumour microenvironment [17], which can cause drug resistance through cell cycle arrest and downregulation of pro-cell death proteins (e.g., caspase-3 in apoptosis) [18].…”
mentioning
confidence: 99%
“…TAMs migrate to the cancer microenvironment as monocytes and are differentiated and polarized at the tumor site, typically to an alternatively activated, or M2, phenotype with angiogenic and ECM remodeling characteristics 57–59. The presence of TAMs are associated with poor prognosis as confirmed for a wide range of solid tumors using histology 59. However, histology alone is unable to capture the dynamic processes of TAM recruitment to the microenvironment and cancer cell invasion following TAM accumulation.…”
Section: Coculture Effects On Cell Movement Through Hydrogelsmentioning
confidence: 99%
“…However, histology alone is unable to capture the dynamic processes of TAM recruitment to the microenvironment and cancer cell invasion following TAM accumulation. Thus, hydrogel disease models incorporating TAMs aim to recapitulate aggressive tumor microenvironments 59–62…”
Section: Coculture Effects On Cell Movement Through Hydrogelsmentioning
confidence: 99%